Macular pigmentation complicating irritant contact dermatitis and viral warts in Laugier–Hunziker syndrome. (28th October 2015) - Bhoyrul, B.; Paulus, J.
Summary: Laugier–Hunziker syndrome (LHS) is a rare acquired disorder characterized by macu‐lar pigmentation of the lips and oral mucosa, with frequent longitudinal melanonychia. Involvement of other areas, such as the genitalia and fingers, has rarely been described. LHS is a benign condition with no known systemic manifestations. We report the case of a woman who developed melanotic macules on her fingers and elbow 16 years after the onset of pigmentation of her lips. This unusual feature of LHS in our patient was associated with irritant contact dermatitis and viral warts. Only two cases of an association with an inflammatory dermatosis have been reported previously in the literature.